Problematika Pembelajaran Daring Bahasa Arab Di Masa Pandemi Covid-19 Siswa Kelas XI MAN 1 Kota Makassar - Sarina Sarina; Hasmawati Hasmawati (Fakultas Teknik Universitas Negeri Makassar, 2021)
The purpose of this study is to find out 1) the process of learning Arabic online during the covid-19 pandemic for students of class MAN 1 Makassar city. 2) the problem of learning Arabic online during the covid-19 pandemic class XI MAN 1 Makassar city students. 3) the effort made to overcome the problems of learning Arabic online during the Covid-19 pandemic for class XI MAN 1 Makassar city students. This study uses a descriptive qualitative approach. Data collection techniques in this study were interview, questionnaire, and documentation techniques. Checking the validity of the data using triangulation of data sources. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. The results of this study conclude that (1) the online learning process consists of planning and implementing learning. Planning by preparing RPP in advance and implementing it using whatsAap and e-learning platforms. (2) the problems of learning Arabic online are internal and external. Internal problems, namely, problems in online learning techniques. There are still many students who have difficulty and do not understand the material, then the problem of motivation and interest. External problems include problems in the family environment, namely there are still parents who do not care about their children's education and problems in the school environment, namely the lack of interaction between students and teachers. (3) Efforts are made to overcome the problems of online learning Arabic during the covid-19 pandemic for class XI MAN 1 students by Arabic language teachers, namely for students who do not understand the material that has been given through online learning, the teacher will hold additional classes scheduled three times per week. Efforts made by students if they do not understand the material, namely watching the material that has been given and asking or discussing with friends.Keywords: problematic, online learning, covid-19.